(3fRgI GdCdHGH GdLGeYI dafhf GdBOGHs - (3GdGOcGhj GdeDPf , YHO Gddg Hf YHO Gddg Hf SdGeI GdTGaYj, GdeDPf,J (B1184 (3g` s
(3ChdgG (B:s
(3MejkG Rjf eMGad GdNdaGA HeMGSf GdCOHGA s
(3BNQgG (B:s
(3heGHQMfG MJi OafGgeG QMeG Gddg Je GdLRA GdChd ef fRgI GdCdHGH s
(3GdfSNI HgG MhGTs
(3HChdgG agQSJs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B99 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B79 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B484s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdCOHs